2007
DOI: 10.1080/10286020500531977
|View full text |Cite
|
Sign up to set email alerts
|

Harzianums A and B produced by a fungal strain, Hypocrea sp. F000527, and their cytotoxicity against tumor cell lines

Abstract: A new compound, harzianum B (1), was isolated from the culture broth of a fungal strain, Hypocrea sp. F000527, together with a known trichothecene, harzianum A (2). Its structure was determined by spectroscopic analyses including HRFAB-MS and various (1)H NMR and (13)C NMR spectral data. Harzianum B (1) was characterised as (E,Z,E)-2', 4', 6'-octatriendioic acid esterified on the 4beta-hydroxyl group of trichodermol. Harzianums A (2) and B (1) showed cytotoxicity against several human cancer cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 5 publications
1
16
1
Order By: Relevance
“…Lee et al (2005) reported production of harzianum A by a strain (F000527 = CBS 113214) isolated directly from a soil sample collected in Daejeon, Korea, and identified by DNA sequences as a Hypocrea sp. Recently, a new trichothecene homologue, harzianum B, was isolated from the same strain (Jin et al 2007). We received this strain too late to include in our phylogenetic analysis, but we have identified it also as T. arundinaceum.…”
Section: Discussionmentioning
confidence: 97%
“…Lee et al (2005) reported production of harzianum A by a strain (F000527 = CBS 113214) isolated directly from a soil sample collected in Daejeon, Korea, and identified by DNA sequences as a Hypocrea sp. Recently, a new trichothecene homologue, harzianum B, was isolated from the same strain (Jin et al 2007). We received this strain too late to include in our phylogenetic analysis, but we have identified it also as T. arundinaceum.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, the solid obtained was resuspended in acetonitrile and stored at Ϫ30°C. HA was identified by nuclear magnetic resonance (NMR) (27) and quantified by using a standard curve.…”
Section: Methodsmentioning
confidence: 99%
“…cDNAs were synthesized by using 1 g of total RNA and a reverse transcription system based on the use of an oligo(dT) 15 primer (Promega, Madison, WI). cDNAs were quantified using a Nanodrop 2000 spectrophotometer (Thermo Scientific, Wilmington, DE).…”
Section: Methodsmentioning
confidence: 99%
“…HA and trichodermin have been studied widely in the last few decades (11)(12)(13)(14)(15)(16), and their biosynthetic pathways have been detailed almost completely (9). Research has expanded to examine the structure-function relationships of the various trichothecenes and their intermediates on plants and other fungi.…”
mentioning
confidence: 99%